METHODOLOGY FOR ASSESSING THE IMPACT OF INFORMATION AND DIGITALIZATION ON AGRICULTURAL DEVELOPMENT (American Journal of Business Management, Economics and Banking, 2024)
The article discusses the methodology for determining the relationship and correspondence between the agricultural development and informatization. Research on the interdependence between agricultural informatization and agricultural economics has shown that they play an important role in mutual assistance and integration. To assess the relationship between the development of agriculture and information technology using the method of entropy values and correlation analysis, a methodology was developed to assess the degree of relationship and compatibility using regional data for a certain period.